Functional Near‐Infrared Spectroscopy to Assess Central Pain Responses in a Nonpharmacologic Treatment Trial of Osteoarthritis. Issue 6 (8th September 2020) - Pollonini, Luca; Montero‐Hernandez, Samuel; Park, Lindsey; Miao, Hongyu; Mathis, Kenneth; Ahn, Hyochol
ABSTRACT: BACKGROUND AND PURPOSE: Knee osteoarthritis (OA) is a common source of pain in older adults. Although OA‐induced pain can be relieved with analgesics and anti‐inflammatory drugs, the current opioid epidemic is fostering the exploration of nonpharmacologic strategies for pain mitigation. Amongs these, transcranial direct current stimulation (tDCS) and mindfulness‐based meditation (MBM) hold potential for pain‐relief efficacy due to their neuromodulatory effects of the central nervous system, which is known to play a fundamental role in pain perception and processing. METHODS: In this double‐blind study, we used functional near‐infrared spectroscopy (fNIRS) to investigate the effects of tDCS combined with MBM on underlying pain processing mechanisms at the central nervous level in older adults with knee OA. Nineteen subjects were randomly assigned to two groups undergoing a 10‐day active tDCS and MBM regimen and a sham tDCS and MBM regimen, respectively. RESULTS: Our results showed that the neuromodulatory intervention significantly relieved pain only in the group receiving active treatment. We also found that only the active treatment group showed a significant increase in oxyhemoglobin activation of the superior motor and somatosensory cortices colocated to the placement of the tDCS anodal electrode. To our knowledge, this is the first study in which the combined effect of tDCS and MBM is investigated using fNIRS. CONCLUSION: In conclusion, fNIRS can be effectively used to investigate neural mechanisms of pain at the cortical level in association with nonpharmacological, self‐administered treatments.